The Velocities of Maximum Escaped Savings with than of Financial Liquidity to the Case of Mixed Savings - Challoumis, Constantinos (Research Parks Publishers, 2023)
This paper is about the comparison of the velocity of the cycle of money with the velocity of financial liquidity in the case of mixed savings. This analysis is based on the cycle of money in combination with the velocity of maximum escaped savings with the velocity of financial liquidity with the influence of mixed savings. This means that used the maximum escaped savings, the enforcement savings, and the mixed savings are parts of these velocities. Thence, we compare the velocity of the financial liquidly with the velocity of the maximum escaped savings, using and the mixed savings. Then, we extract conclusions between these velocities. The method used is the Q.E. method.